Determinants of School Enrolment of Children in Slums of Varanasi - Nayak, Pallavi; Singh, Payal; Tripathi, Neeraj; Mishra, Akash; Mishra, R N (Indian Journal of Community Health, 2016)
Introduction: Education plays a vital role to developing a nation. In India, urban slums constituting about 22.6% of the urban population are the poor and socially disadvantaged. This slum community is least concerned for school enrolment of their children inspite of the fact that primary education is compulsory and is free in public schools. In urban areas schools available are mostly of private sector that are not free and beyond affordability to slums; government and corporation schools are few, but beyond reach. Motive of the parents is to involve children in income generating activities and the girls are more deprived of school enrolment in poorer society. Objectives: 1) assess the enrolment status of slum children and 2) determine the factors influencing school enrolment. Methodology: The data was collected during 2011-12 from 15 randomly selected slums out of 227 in which a total of 893 families were contacted and mothers with children aged 5-15 years interrogated. In addition to child history on age, sex and school enrolment, the family background characteristics were e.g. religion, caste, and family size as well as age, education and occupation of both mother & father were recorded. Results: Out of 1145 children, male and female equal represented; mostly (90.9%) were Hindus and half were SC/ST class. About 30% father and 57.2% mothers were illiterate; about half fathers were unskilled-worker and 96.0% mother’s house wife. Overall 31.3% children were not enrolled and were decreasing from 49.2% to 24.3% to 21.4% in the age groups 5-6, 7-9 and 10-15 years respectively. Enrolment was poor in Muslims (50.0%) compared to Hindus (29.4%); enrolment was similar irrespective of child sex among Hindus, but in Muslims 62.5% male and 35.4% female children were only enrolled. Similar was the situation as one move from SC/ST (67.6%) to OBC (73.4%) and general caste (77.9%). Education of father and mother had significant role to enrolment but not the age and occupation of father and mother. Female child enrolment was poor if father was in business and mother was aged. Logistic regression analysis indicated that school enrolment of children aged 5-7 years was associated with age of mother and educational combination of father and mother, while of children 8-15 years caste/religion, family size, sex of child and educational combination of father and mother were found associated. Conclusion: Findings suggest that slum community as a whole is the pocket constituted by habitats of socially disadvantaged class has to be promoted with attitudinal change to schooling of their children without discriminating child sex.